FAKTOR-FAKTOR YANG MEMPENGARUHI PENYUSUNAN ANGGARAN BELANJA BERBASIS KINERJA DI PEMERINTAH PROVINSI PAPUA BARAT - Nengsi Oktavia Makalew; Paulus Kombo Allo Layuk; Ida Ayu Purba Riani (Universitas Cenderawasih, 2021)
This study aims to determine the effect of partially and simultaneously between Human Resources Competence, Organizational Commitment, and Appreciation on Performance-Based Budgeting in the Regional Organizations of West Papua Province Government. The sample in this study were 96 employees. The analytical tool in this study is multiple linear regression using the SPSS Program.The results showed that; 1) Partially independent variables (HR competencies and rewards influence the preparation of performance-based budgeting in the Regional Government of West Papua Province. 2). Together / simultaneously Human resource competency variables, organizational commitment, and rewards influence the preparation of performance-based budgeting in the Regional Government of West Papua Province. 3). The dominant variable influencing performance-based budgeting in the West Papua Provincial Government is the award.